Relationship between Pessimism, General Health and Emotional Intelligence in College Students at Shiraz University and Shiraz University of Medical Sciences - K Banihashemian (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Behaviors, habits and life style have obvious effectiveness on human health. Also emotional features have direct relationship with general health. The aim of this study was to compare the relationship between pessimism, general health and emotional intelligence in college students at Shiraz University and Shiraz University of medical sciences. METHODS: This cross sectional study was performed on 203 college students (88 males and 115 females), at Shiraz University of medical sciences, and 201 college students (95 males and 106 females) at Shiraz University. They were randomly selected. Students completed Beck hopelessness scale (20-items), emotional intelligence (33-items), and Goldberg general health (28-items) questionnaires. Pearson correlation coefficient, independent t-test, and multiple regression analysis were used.FINDINGS: Pessimism and general health in medical college students were 11.3±4 and 28±20.6, respectively. Pessimism and general health in non-medical college students were 9.7±3.4 and 49±25.2, respectively that there was a significant relationship between pessimism and general health in both groups of students (p< 0.001). Also emotional intelligence in medical college students was 124.8±11.7 and in non-medical college students was 129.7±11.2 that there was a significant relationship between emotional intelligence and general health (p<0.001).CONCLUSION: The results of this study showed that pessimism in medical college students is more than non-medical college students and general health and emotional intelligence in medical college students are less than non-medical college students. So it is recommended to use psychological method for removing pessimism and improving general health in medical college students.